2007
DOI: 10.1242/jeb.02746
|View full text |Cite
|
Sign up to set email alerts
|

The aerodynamic benefit of wing–wing interaction depends on stroke trajectory in flapping insect wings

Abstract: SUMMARY Flying insects may enhance their flight force production by contralateral wing interaction during dorsal stroke reversal (`clap-and-fling'). In this study, we explored the forces and moments due to clap-and-fling at various wing tip trajectories, employing a dynamically scaled electromechanical flapping device. The 17 tested bio-inspired kinematic patterns were identical in stroke amplitude, stroke frequency and angle of attack with respect to the horizontal stroke plane but varied in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 47 publications
2
53
2
Order By: Relevance
“…It has further been shown that a delay in timing of wing rotation during the dorsal and ventral stroke reversal may attenuate force generation (Dickinson et al, 1999;Sane and Dickinson, 2002) and most insects such as beetles (Coccinella), dipterans (Calliphora, Tipula and Eristalis) and hymenopterans (Apis and Bombus) exhibit rather symmetrical wing rotation, in which 50% of the change in angle of attack occurs before and after each stroke reversal, respectively (Ellington, 1984b;Nachtigall, 1966). We modelled wing kinematics in this study close to the patterns mentioned above and similar to the patterns used in other experimental and numerical studies on dipteran flight: 150Hz stroke frequency, 135deg flapping amplitude in a flat horizontal stroke plane, symmetrical wing rotation (equal rotational time during upstroke and downstroke), and an angle of attack at mid stroke of 40 and 20deg during downstroke and upstroke, respectively (Dickinson et al, 1999;Lehmann and Pick, 2007) (Fig.2). Using a rotational axis for wing rotation at 28.6% mean wing chord length (see Rotational wing axis), our kinematic pattern produces a mean vertical force opposite to gravity of 596N (two wings), supporting the fly's body weight within 2.8% accuracy (body mass, 59.1±10.2mg, mean ±s.d., N10 C. vicina).…”
Section: Wing Kinematicsmentioning
confidence: 81%
See 1 more Smart Citation
“…It has further been shown that a delay in timing of wing rotation during the dorsal and ventral stroke reversal may attenuate force generation (Dickinson et al, 1999;Sane and Dickinson, 2002) and most insects such as beetles (Coccinella), dipterans (Calliphora, Tipula and Eristalis) and hymenopterans (Apis and Bombus) exhibit rather symmetrical wing rotation, in which 50% of the change in angle of attack occurs before and after each stroke reversal, respectively (Ellington, 1984b;Nachtigall, 1966). We modelled wing kinematics in this study close to the patterns mentioned above and similar to the patterns used in other experimental and numerical studies on dipteran flight: 150Hz stroke frequency, 135deg flapping amplitude in a flat horizontal stroke plane, symmetrical wing rotation (equal rotational time during upstroke and downstroke), and an angle of attack at mid stroke of 40 and 20deg during downstroke and upstroke, respectively (Dickinson et al, 1999;Lehmann and Pick, 2007) (Fig.2). Using a rotational axis for wing rotation at 28.6% mean wing chord length (see Rotational wing axis), our kinematic pattern produces a mean vertical force opposite to gravity of 596N (two wings), supporting the fly's body weight within 2.8% accuracy (body mass, 59.1±10.2mg, mean ±s.d., N10 C. vicina).…”
Section: Wing Kinematicsmentioning
confidence: 81%
“…According to Ellington (Ellington, 1984b) and Lehmann and Pick (Lehmann and Pick, 2007), inertial forces due to translational acceleration of the wing in the horizontal (F* i,h ) are given by:…”
Section: Appendixmentioning
confidence: 99%
“…Previous research has also shown that this stroke results in a large attached leading edge vortex on each wing, which leads to larger lift forces (Lighthill, 1973;Maxworthy, 1979;Spedding and Maxworthy, 1986;Lehmann et al, 2005;Peskin, 2005, 2009;Lehmann and Pick, 2007). However, it is possible that clap and fling may naturally result from an increase in wing stroke amplitude to make up for a decrease in wing area as the size of the insect decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the upward motion during clap, the foil is pulled tight during the rotation. The downward leading edge motion during peel might reinforce the leading edge vortex generation by increasing the velocity of the fluid moving into the opening gap 33 .…”
Section: Heaving Motionmentioning
confidence: 99%